The new generation of intravenous iron: chemistry, pharmacology, and toxicology of ferric carboxymaltose - Funk, Felix; Ryle, Peter; Canclini, Camillo; Neiser, Susann; Geisser, Peter (Arzneimittelforschung, 2010)
An ideal preparation for intravenous iron replacement therapy should balance effectiveness and safety. Compounds that release iron rapidly tend to cause toxicity, while large molecules can induce antibody formation and cause anaphylactic reactions. There is therefore a need for an intravenous iron preparation that delivers appropriate amounts of iron in a readily available form but with minimal side effects and thus with an excellent safety profile. In this paper, a review is given on the chemistry, pharmacology, and toxicology of ferric carboxymaltose (FCM, Ferinject®), a stable and robust complex formulated as a colloidal solution with a physiological pH.The complex is gradually taken up mainly from the hepatic reticulo-endo-thelial system (RES), followed by effective delivery of iron to the endogeneous transport system for the haem synthesis in new erythrocytes, as shown in studies on the pharmacodynamics and pharmacokinetics with radio-labelled FCM. Studies with radio-labelled FCM also demonstrated a barrier function of the placenta and a low transfer of iron into the milk of lactating rats. Safety pharmacology studies indicated a favourable profile with regard to cardiovascular, central nervous, respiratory, and renal toxicity. A high maximum non-lethal dose was demonstrated in the single-dose toxicity studies. Furthermore, based on the No-Observed-Adverse-Effect-Levels (NOAELs) found in repeated-dose toxicity studies and on the cumulative doses administered, FCM has good safety margins. Reproductive and developmental toxicity studies did not reveal any direct or indirect harmful effects. No genotoxic potential was found in in vitro or in vivo studies. Moreover, antigenicity studies showed no cross-reactivity of FMC with anti-dextran antibodies and also suggested that FCM does not possess sensitizing potential. Lastly, no evidence of irritation was found in local tolerance studies with FCM.This excellent toxicity profile and the high effectiveness of FCM allow the administration of high doses as a single infusion or bolus injection, which will enhance the cost-effectiveness and convenience of iron replacement therapy. In conclusion, FCM has many of the characteristics of an ideal intravenous iron preparation.
Keywords: Anaemia; Ferinject®; Ferric carboxymaltose, chemistry, pharmacology, toxicology; Intravenous iron; Iron deficiency